2022
DOI: 10.3389/fimmu.2022.878195
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-Based Dissection of Intracranial Aneurysms Unveils an “Immuno-Thermal” Microenvironment and Defines a Pathological Feature-Derived Gene Signature for Risk Estimation

Abstract: Immune inflammation plays an essential role in the formation and rupture of intracranial aneurysm (IA). However, the current limited knowledge of alterations in the immune microenvironment of IA has hampered the mastery of pathological mechanisms and technological advances, such as molecular diagnostic and coated stent-based molecular therapy. In this study, seven IA datasets were enrolled from the GEO database to decode the immune microenvironment and relevant biometric alterations. The ssGSEA algorithm was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…used WGCNA and ssGSEA methods to analyze IA and normal samples and identified immune-related genes that mediate IA. The final results showed that inflammation and immune responses are involved in IA pathogenesis ( 23 ).…”
Section: Discussionmentioning
confidence: 98%
“…used WGCNA and ssGSEA methods to analyze IA and normal samples and identified immune-related genes that mediate IA. The final results showed that inflammation and immune responses are involved in IA pathogenesis ( 23 ).…”
Section: Discussionmentioning
confidence: 98%
“…Along with the development of bioinformatic tools appeared a new type of study presenting re-analyzed data from available datasets, including expression data from the Gene Expression Omnibus (GEO). Approximately one third of these published secondary analyses utilized a single dataset [ 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ] and two thirds leveraged data from two to eight datasets [ 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. These studies did not provide any new additional clinical data but rather aimed to deepen the insight into molecular mechanisms of the IA pathophysiology by revealing key regulatory networks and interactions between investigated molecules.…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%
“…Although differential expression and functional annotation were examined, further analyses of co-expression networks with identification of hub RNA molecules, competing endogenous RNA (ceRNA) networks, or protein–protein interaction (PPI) networks became a standard approach. In some of these studies, specific areas of interest were predefined, such as: epithelial–mesenchymal transition [ 78 ], endoplasmic reticulum stress [ 81 ], immune environment [ 79 , 83 ], or ferroptosis [ 84 , 85 ]. In three studies, an attempt was made to identify potential therapeutic targets [ 71 , 82 , 83 ].…”
Section: Studies Based On Existing Datasetsmentioning
confidence: 99%
See 1 more Smart Citation
“…The gene set for marking 28 immune cell types was enrolled from a previously published article (19) and illustrated in Supplementary Table S2. Then, the relative infiltration abundance of immune cells in OA and normal synovium was estimated by the ssGSEA algorithm implemented in the GSVA R package, which is broadly utilized in immune infiltration-related bioinformatics studies (20)(21)(22)(23).…”
Section: Immune Cell Infiltration Estimationmentioning
confidence: 99%